(untitled) (Philology, 2026)
The article discusses the work of Dionysius of Halicarnassus On Composition in the context of literary criticism and grammatical studies in the Hellenistic period. After a brief overview of the tradition in the study of language and literary art in Antiquity, the article highlights the concept of combining sounds and syllables to achieve beauty and pleasure as the ultimate aim of the poet. The focus of the work is on four of the 26 chapters of the treatise, which contain important evidence of ancient Greek phonetics and phonology, which elegantly incorporate Dionysus’ analysis of exemplary verses of Homer’s Iliad and Odyssey.